Worm humus as a confining treatment for cadmium-contaminated soils in the Loreto Region, Peru - Ríos Paima, Kiara Melissa (2025)
Research on cadmium contamination in agricultural soils has gained significant relevance by demonstrating that organic amendments are effective in immobilizing cadmium. In this study, the species brizanta (Brachiaria brizantha), a grass used in livestock activities, was selected and studied as a phytoremediation plant. The objective was to evaluate the effectiveness of earthworm humus in the remediation of cadmium contaminated soils, using Brachiaria brizantha as a biological indicator in the city of Yurimaguas. For the method, a randomized experiment was designed with four treatments: a control without humus (T0) and three doses of worm humus (T1: 5000g/m², T2: 10000g/m², T3: 15000g/m²) in soils with 1.5 ppm of cadmium. Plant growth and cadmium concentrations were monitored for four months. The results showed that T3 retained more cadmium in the soil (0.4467 mg/kg), while T2 and T0 presented greater accumulation in the plants (1.3367 mg/kg and 1.0367 mg/kg, respectively). A significant negative correlation was observed between cadmium in soil and plant (r=-0.714, p=0.009), and although there were no significant differences in growth, the relationship between cadmium in plant and dry weight (r=-0.620, p=0.031) suggests phytotoxic effects. It is concluded that vermicompost can modify the bioavailability of cadmium, offering a viable alternative for the remediation of soils contaminated with heavy metals. Likewise, the correlation of cadmium in the plant and dry weight does not significantly influence, indicating that as dry weight increases, the cadmium concentration of the plant decreases.